QUALIMETRIC APPROACH TO EVALUATING DIGITAL COMPETENCIES OF TEACHERS - Chorosova, O.M.; Protodyakonova, G.Yu.; Gerasimova, R.E.; Aetdinova, R.R.; Niyazbekova, Sh.; Zakharov, N.T. (Scientific Journal of Pedagogy and Economics, 2020)
The article is devoted to the study of the problems of the formation and evaluation of digital competencies in the context of digitalization of general education. Currently, the problem of determining the level of formation of competencies among specialists in any field is an urgent task in the preparation and competitive selection of specialists. In the Russian education system, the training of future teachers and advanced training, additional professional education of experienced teachers should go to a new level of development in connection with the implementation of competency-based educational programs. And in these conditions, it becomes necessary to search for new approaches to assessing professional and digital competencies in general education teachers. Various models and algorithms for the formation of professional and digital competencies in general education teachers are studied. The approaches to the development of a cognitive model of competency formation are identified. A qualimetric approach to assessing digital competencies is revealed, as one of the most effective. Descriptors of key competencies of the digital economy, digital competencies are developed. The criteria for assessing digital and professional competencies formed by general education teachers were identified, the main indicators for evaluating the results were determined. A mechanism and means for assessing the level of formation of digital competencies, a scale for translating assessments of the level of competencies into a verbal assessment system have been developed. Based on the main indicators for assessing results, competency matrices have been developed for all stages of competency formation. An appraisal fund has been developed, consisting of various competency-level appraisals that have both formative and appraisal functions. This study allows us to develop a cognitive model of the formation of the digital competence of a teacher in the context of digitalization of general education. The results of the study can become the basis for the modernization of the system of training and retraining of teachers in the context of digitalization of general education.